2005
DOI: 10.1093/nar/gki248
|View full text |Cite
|
Sign up to set email alerts
|

Leaky ribosomal scanning in mammalian genomes: significance of histone H4 alternative translation in vivo

Abstract: Like alternative splicing, leaky ribosomal scanning (LRS), which occurs at suboptimal translational initiation codons, increases the physiological flexibility of the genome by allowing alternative translation. Comprehensive analysis of 22 208 human mRNAs indicates that, although the most important positions relative to the first nucleotide of the initiation codon, −3 and +4, are usually such that support initiation (A−3 = 42%, G−3 = 36% and G+4 = 47%), only 37.4% of the genes adhere to the purine (R)−3/G+4 rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…(27) Similarly, alternative TISs and leaky scanning are responsible for synthesis of mitochondrial and cytoplasmic isoforms of rat ornithine decarboxylase-antizyme and human insulin-degrading enzyme, secretory and mitochondrial isoforms of human neuropeptide Y, nuclear and secretory isoforms of parathyroid hormone-related peptide, synthesis of histone H4 and osteogenic growth peptide from single mRNA. (28)(29)(30)(31)(32)(33) mRNAs of regulatory genes often contain alternative TISs and encode functionally important protein isoforms The mRNA of human transcription factor MDM2 produces several protein isoforms (p90 and p75). It was found that p75 is in fact a mixture of two separate N-terminally truncated proteins that, respectively, lack either the first 61 or 101 amino acids and are produced by initiation of protein synthesis at internal AUG codons at position 62 or 102.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…(27) Similarly, alternative TISs and leaky scanning are responsible for synthesis of mitochondrial and cytoplasmic isoforms of rat ornithine decarboxylase-antizyme and human insulin-degrading enzyme, secretory and mitochondrial isoforms of human neuropeptide Y, nuclear and secretory isoforms of parathyroid hormone-related peptide, synthesis of histone H4 and osteogenic growth peptide from single mRNA. (28)(29)(30)(31)(32)(33) mRNAs of regulatory genes often contain alternative TISs and encode functionally important protein isoforms The mRNA of human transcription factor MDM2 produces several protein isoforms (p90 and p75). It was found that p75 is in fact a mixture of two separate N-terminally truncated proteins that, respectively, lack either the first 61 or 101 amino acids and are produced by initiation of protein synthesis at internal AUG codons at position 62 or 102.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%
“…First, the optimal Kozak sequence 5Ј-CRCCAUGG-3Ј (Smith et al 2005) is different from the YY1 consensus in several positions (CAA GATGGCGGC, differences underlined). In particular, the four positions at the 3Ј end of the YY1 consensus (CGGC) are not required for the Kozak sequence.…”
Section: The Yy1 Motif Overlaps With the Kozak Sequencementioning
confidence: 99%
“…Second, the human Kozak sequence is much more degenerate than the YY1 motif. In a recent study, when the nucleotides flanking the AUG start codon for 22,208 human genes were aligned, weak consensus was observed only for the -3 and +4 positions (5Ј-NRNNAUGG-3Ј) (Smith et al 2005). In contrast, the YY1 motif has high information content at most positions (Table 1; the YY1 PSSM is provided in Supplemental Materials).…”
Section: The Yy1 Motif Overlaps With the Kozak Sequencementioning
confidence: 99%
“…Many of the upstream AUGs initiate short ORFs embedded in the 59-UTR, and, although they are mostly thought to regulate the expression of the main ORF (Kozak 2002;Churbanov et al 2005;Hinnebusch 2005;Iacono et al 2005), it is possible that some encode short biologically active peptides (Oyama et al 2004). Considering potential alternative initiation downstream from the primary initiation site, the abundance of mRNAs whose 59-most AUG triplets are in suboptimal contexts (absence of a purine at ÿ3 and/or G at +4) has suggested that as many as half of human mRNAs could express more than one polypeptide through a leaky scanning mechanism; this would seem especially likely for the 12.5% of mRNAs lacking both purine at ÿ3 and G at +4 (Smith et al 2005). Many of these hypothetical cases would be expected to involve the production of small peptides that have routinely been excluded from sequence annotations and protein preparations and thus have received scant experimental attention.…”
Section: Introductionmentioning
confidence: 99%